DISQUISITIONS ON ORIGINAL ANTIGENIC SIN : II. PROOF IN LOWER CREATURES - de St.Groth, S. Fazekas (The Rockefeller University Press, 1966)
Experiments in rabbits were designed to test the two unproven assumptions of the hypothesis proposed in the companion paper (1): that Original Antigenic Sin is fundamentally a restricted anamnestic response, and that there exists a trapping mechanism capable of deflecting antigen from one kind of cell and guiding it to another. It is shown that whole-body X-irradiation, sufficient to abolish primary but not secondary production of antibodies, leaves all manifestations of the Original Antigenic Sin untouched. This proves the first assumption. Primary immune animals challenged with very large doses of a related antigen produce an immediate response of cross-reactive antibodies, followed by a standard primary response to the challenging antigen. When boosted with an appropriate mixture of both antigens, the response is of standard secondary type to the homologous antigen, followed by a standard primary response to the crossreacting antigen. When animals are primarily vaccinated with a mixture of two related antigens, small booster doses of either will stimulate a standard secondary response only. When such animals are given very large booster doses of either antigen, the response is a compound of a homologous secondary and of an Original Antigenic Sin-type against the related antigen. Each of these findings demonstrates a corollary of the second assumption. The results are discussed in terms of the limitations they impose on theories concerned with the production of antibodies.